Case study of two post vaccination SARS-CoV-2 infections with P1 variants in coronavac vaccinees in Brazil - Estofolete, Cassia F.; Banho, Cecilia A.; Campos, Guilherme R.F.; Marques, Beatriz C.; Sacchetto, Livia; Ullmann, Leila S. [UNESP]; Possebon, Fabio S. [UNESP]; Machado, Luana F.; Syrio, Juliana D.; Araújo Junior, João P. [UNESP]; Bittar, Cintia [UNESP]; Rahal, Paula [UNESP]; et al. (MDPI, 2021)
The rapid development of efficacious and safe vaccines against coronavirus disease 2019 (COVID-19) has been instrumental in mitigating the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Moreover, the emergence of SARS-CoV-2 variants raised concerns on the efficacy of these vaccines. Herein, we report two cases of breakthrough infections with the P1 variant in patients vaccinated with CoronaVac, which is one of the two vaccines authorized for emergency use in the Brazilian immunization program. Our observations suggest that the vaccine reduced the severity of the disease and highlight the potential risk of illness following vaccination and subsequent infection with the P1 variant as well as for continued efforts to prevent and diagnose infection in vaccinated persons.
Keywords: COVID-19; SARS-CoV-2; Vaccine